Comparative Fluoride Release and Antimicrobial Analysis of Commercial and Experimental Bioactive Glass/Nano-Oxide-Based Dentifrices - Gul, Hashmat; Nayyer, Maleeha; Gilani, Mehreen; Aman, Nadia; Azad, Azad Ali; Shah, Asma Tufail; Chaudhry, Aqif Anwar; Kaleem, Muhammad; Khan, Abdul Samad (European Journal of Dentistry, 2020)
Objectives The objectives were to measure fluoride release and assess the antimicrobial behavior of fluoride-doped nano bioactive glass (F-nBG) and nano zinc oxide (ZnO)-enriched novel dentifrices.Materials and Methods Experimental dentifrices were synthesized by incorporating ZnO nanoparticles and F-nBG (1.5 wt% and 4 wt%) as active ingredients. The fluoride release behavior of suspensions and elutes of samples were analyzed by ion selective electrode. Antimicrobial activity and minimum bactericidal concentration against Streptococcus mutans and Lactobacillus casei were evaluated. Microbial stability against contamination was also assessed by a challenge test.Results The fluoride release behavior of experimental dentifrices was higher than that of commercial dentifrices and was dependent on filler loading. The fluoride release was more from suspensions than elutes. Zones of inhibition (ZOIs) and minimum bactericidal concentration values for novel dentifrices showed direct proportionality with filler loading, and effectiveness was exhibited against both strains. Experimental dentifrices exhibited effective antibacterial potential, which could possibly be due to release of sufficient fluoride and zinc ions in aqueous media from F-nBG and ZnO present in their formulations.Conclusion Combination of F-nBG and ZnO may provide a multi-benefit approach for simultaneously treating early white spot lesions, reducing bacterial growth, and providing core plaque control.
Keywords: toothpaste; nanoparticles; bioactive glass; zinc oxide; fluoride release; antibacterial